2010
DOI: 10.1016/s1684-1182(10)60079-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic Pleurodynia Caused by Coxsackievirus B3 at a Medical Center in Northern Taiwan

Abstract: Epidemic pleurodynia is seldom reported in Southeast Asia and there has been no report from Taiwan. We conducted a retrospective chart review of children = 18 years of age in the National Taiwan University Hospital from January 1 to December 31, 2005. Epidemic pleurodynia was defined as an acute illness characterized by sharp localized pain over the chest or upper abdomen. Patients with known heart diseases or pulmonary consolidations were excluded. In total, 28 patients met the case definition of epidemic ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…It is possible that the reason why acute low back pain has not been previously reported as a symptom of epidemic myalgia is that the disease was first described many years ago, which may have limited the number of further reports regarding novel symptoms. Moreover, there is low awareness regarding this disease in East Asia [7, 8]. Furthermore, this disease is difficult to recognize, and thus many cases go unreported [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the reason why acute low back pain has not been previously reported as a symptom of epidemic myalgia is that the disease was first described many years ago, which may have limited the number of further reports regarding novel symptoms. Moreover, there is low awareness regarding this disease in East Asia [7, 8]. Furthermore, this disease is difficult to recognize, and thus many cases go unreported [7].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is low awareness regarding this disease in East Asia [7, 8]. Furthermore, this disease is difficult to recognize, and thus many cases go unreported [7]. Finally, non-steroidal anti-inflammatory drugs are effective against epidemic myalgia pain [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, a few laboratory findings can aid in the diagnosis. A full blood count could show a picture of leucopenia or leucocytosis with or without elevated band cells,5 but a normal WCC is not uncommon. There are also a number of reports of elevated erythrocyte sedimentation and creatine kinase.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several reports of positive lung infiltrates with or without pleural effusion as was the case with our patient. Huang et al 5 reported that 45% of patients with Bornholm disease had positive chest radiological findings.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known as Bornholm disease or epidemic pleurodinia . It may cause pulmonary in fi ltrates, involve the pleura producing pleural effusions or affect the nearby tissues causing myositis of the abdominal and intercostal muscles and even myopericarditis [ 73 ] . It causes intermittent chest pain that increases with deep respiration, frequently associated with fever in young adults [ 49 ] .…”
Section: Epidemic Myalgiamentioning
confidence: 99%